Internet of things system design - Freddy Kusnandar Santoso (2015)
Security in the Internet of Things is an important issue to consider as the adoption of Internet of Things has spread to many applications, including smart home system. The unique environment of smart home system presents a different requirement set for Internet of Things. Wireless technology used in the system requires a stronger approach to device authentication. User convenience is a necessary requirement in the security strategy of smart home systems. This project designs and implements an Internet of Things system for smart home using the existing IPv4 home Wi-Fi network. Using the AllJoyn framework as the base, the system uses a gateway to provide a better authentication process and a convenient interface for the user via an Android device.